A Combination of Patient-Related Factors and Surgical Parameters Distinguishes Best and Worst Outcomes of ASD Surgery - Rizzo, Toni (MD Conference Express, 2015)
To date, evidence suggests that surgical treatment can improve pain and disability in adults with symptomatic scoliosis. However, these studies are based on averages across large groups of patients, and not all surgically treated patients achieve average or above-average outcomes. The reasons that some adults with scoliosis markedly improve with surgery, while others fail to improve, are not clear. The objective of this prospective study, as discussed in this article, was to compare best vs worst clinical outcomes in patients with adult spinal deformity following surgical treatment.